FACTORS INFLUENCING HUMAN BEHAVIOR FROM THE PERSPECTIVE OF COMMUNICATION PSYCHOLOGY - Muhammad Shulton; Feggy Nurdiyansah; Umi Halwati (Indonesian Journal of Islamic Communication, 2025)
This research aims to examine the factors influencing human behavior through a literature study approach by analyzing relevant recent scientific literature. The method used is a qualitative review that involves collecting and analyzing journals focused on the interaction of internal factors—including biological, psychological, and cognitive aspects—with external factors such as social environment, culture, technology, and architectural design. The study findings reveal that human behavior is a complex result of dynamic interactions between innate factors and experiences shaped by social environment and physical conditions. Internal and external factors influence each other in forming adaptive behavior patterns according to diverse cultural and environmental contexts. These findings underscore the importance of a multidimensional approach in understanding human behavior, integrating personal and contextual aspects. The recommendation is to implement inclusive, culturally adaptive, and context-responsive policies and human resource development programs to support positive and sustainable behavioral change.